Perinatal Antidepressant Use: Understanding Women’s Preferences and Concerns - BATTLE, CYNTHIA L. (J Psychiatr Pract, 2013)
Perinatal depression is prevalent and linked with a host of adverse consequences for women and newborns. Rates of engagement in depression treatment are, however, strikingly low among pregnant and postpartum women, with the majority of affected women receiving no mental health treatment. Research indicates that perinatal women are extremely reluctant to take antidepressant medications, yet the nature of women’s concerns and treatment decisionmaking patterns have not been well documented. Developing a clearer understanding of women’s treatment preferences and behaviors may help identify solutions to the under-treatment of perinatal depression. In this mixed methods study, we conducted in-depth interviews with 61 pregnant women, approximately half of whom were experiencing clinical levels of depression. In addition to assessing psychiatric diagnoses, symptoms, and functional impairment, we conducted qualitative interviews addressing women’s preferences for depression treatment, concerns, and decision-making patterns. Consistent with prior reports, women were significantly more likely to voice a preference for non-pharmacologic depression treatments, as opposed to antidepressant medications. Many depressed women reported a great degree of uncertainty regarding how to treat their depression, and those with more severe depression symptoms were more likely to endorse decisional conflict. Analysis of qualitative comments yielded detailed information about the nature of women’s concerns and preferences related to use of antidepressant medications and other aspects of treatment engagement. We discuss findings in the context of improving patient-centered care for perinatal depression.